Shallow-water reef ophiuroids (Echinodermata: Ophiuroidea) of Réunion (Mascarene Islands), with biogeographic considerations - Boissin, Emilie; Hoareau, Thierry B.; Paulay, Gustav; Bruggemann, J. Henrich (Zootaxa, 2016)
Despite their importance in marine biodiversity, invertebrates are far less studied than vertebrates. Given the current global biodiversity crisis and insufficient taxonomic resources, sustained efforts need to be undertaken to assess species diversity, especially in the highly threatened ‘biodiversity hotspots’. Réunion is a young volcanic island lying in the Mascarene Islands (south-western Indian Ocean, SWIO), a marine biodiversity hotspot. A substantial sampling effort was conducted around Réunion Island to document shallow water reef-associated ophiuroid (brittle-stars) diversity, a class recognised as the most diverse among echinoderms. A total of 33 species were documented, increasing the known species richness of the island by 56%. Findings include 15 new records for Réunion, 11 for the Mascarene Islands and 8 for the Indian Ocean. The most diverse family was Ophiocomidae, a family of large, abundant and conspicuous tropical species. Even in this well studied family, a new species was revealed by this survey. Morphological variants together with DNA sequence variations within several species revealed cryptic species. We compared our results with the known fauna of other Mascarene Islands and discuss biogeographic implications for the region.